Equine infectios anemia of traction equids in the Cuiaba Districty, MT, Brazil - Perecin Nociti, Darci Lara; Senna, Denise; Pereira Rego, Caroline Lemes; Hofmeister, Katiane dos Santos; Mutzenberg, Emmanuelle Rosa; Nociti, Ricardo Perecin [UNESP] (Soc Medicina Veterinaria Estado Rio de Janeiro, 2007)
The present study it had for objective to search the AIE in equids traction of the city of Cuiaba, of which if it extracted an inquiry epidemiologist and a sampling of blood serum of 113 animals (110 equines and 3 mules) that they transited for the public ways. The sampling of the animals was random how much to the age (of 8 months the 20 years) and sex of the animals where 67 (60.9%) were of females and 46 (41.8%), of males, with a average of 22 working hours per week. The samples of blood had been analyzed by means of the technique of AGID test. The results of the blood tests had indicated that of the 110 examined samples of blood serum of the equines, thirteen (11.8%) were positive, being seven of female (10.4% of the total of females) and 6 males (13.0% of the total of males), all no symptoms animals and the age of the positive animals was concentrated in the band of 6 10 years, representing 84.6% (11 animals). The results of the blood tests had also indicated that of three mules analyzed, 1 (33.3%) was positive.
Keywords: equine infectious anemia; EIA; equids traction; virus